1992
DOI: 10.3181/00379727-199-43378
|View full text |Cite
|
Sign up to set email alerts
|

Does Aging Affect Liver Microtubules?

Abstract: Microtubules are essential for many cell processes, e.g., ligand-receptor endocytosis and the vectorial movement of endosomes. The cytoskeleton, particularly microtubules, may undergo age-related changes that are reflected in cell dysfunctions. For example, the translocation of 125I-IgA-containing vesicles from the sinusoidal surface to the pericanalicular cytoplasm is reduced (greater than 40%) in old versus young rats. Electron microscopic analysis demonstrated that the concentration of microtubule profiles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…In old rats, apoE was found to be more strongly co-localized with early endosomes and microtubules compared with young rats. As far as we are aware, the effect of old age on the trafficking of apoE has not been reported previously, however, the results are consistent with reports of altered microtubule function and structure in old age (Cash et al 2003;Rao and Cohen 1990;Taylor et al 1992). It is plausible that age-related co-localization of apoE in early endosomes and increased cytoplasmic staining is a consequence of impaired of microtubule function in hepatocytes.…”
Section: Discussionsupporting
confidence: 82%
“…In old rats, apoE was found to be more strongly co-localized with early endosomes and microtubules compared with young rats. As far as we are aware, the effect of old age on the trafficking of apoE has not been reported previously, however, the results are consistent with reports of altered microtubule function and structure in old age (Cash et al 2003;Rao and Cohen 1990;Taylor et al 1992). It is plausible that age-related co-localization of apoE in early endosomes and increased cytoplasmic staining is a consequence of impaired of microtubule function in hepatocytes.…”
Section: Discussionsupporting
confidence: 82%
“…The matrix secreted by old cells exhibits quantitative and structural changes, which is why these cells are less capable of mediating cell adhesion, cell spreading and focal contact formation compared to young cells (136, 137), all of which are significant for intercellular communication, development and dissemination of diseases. Ageing cells are accompanied by disturbances of microtubule metabolism and functions indicative of fewer and/or shorter microtubules (IV, 113, 142–145). The major microfilament actin increases, and the cytoskeletal structures become more rigid in senescent cells (146).…”
Section: Methodological Aspectsmentioning
confidence: 99%
“…Ageing tubulin accumulates isoaspartyl sites and forms disulfide cross‐links between subunits (144) which may disrupt the function of the microtubules. The age‐related decline in tubulin concentration (IV, 143), as well as the increase in the free to total tubulin ratio (143) may be indicative of fewer intact microtubules as shown by immunofluorescence (IV).…”
Section: Herpes Simplex Virus‐cell Interactionsmentioning
confidence: 99%
“…86 The declines in total and polymerized tubulin, together with the increases in the free fractions of microtubule-associated proteins, indicate fewer and/or shorter microtubules in old rats. 87 Microtubules are highly dynamic and the mechanical properties of microtubules are very important for their function. 88 Both experimental and modeling studies demonstrated that aging microtubules have a higher catastrophe rate for switching from assembly to shortening than younger microtubules.…”
Section: Changes In Cytoskeletonmentioning
confidence: 99%
“…Thus, pathological aging-accompanied perturbations of microtubule functions can lead to diseases, such as AD, muscular atrophy, cardiac dysfunction, and cancer. 86,87,92 Apart from actin filaments and microtubules, intermediate filaments serve as the most durable component responsible for stabilizing cellular organelles from the effects of mechanically induced stress. Overexpression of intermediate filaments was observed in human dermal fibroblasts derived from the old donors compared with those from young and newborn donors.…”
Section: Changes In Cytoskeletonmentioning
confidence: 99%